The effect of anastrozole on the single-dose pharmacokinetics and anticoagulant activity of warfarin in healthy volunteers - Yates, R A (Blackwell Science Inc, 2001)
AIMS: The aims of this study were to determine the effects of the nonsteroidal, selective aromatase inhibitor, anastrozole, at steady-state concentrations, on the pharmacokinetics and pharmacodynamics of warfarin, and to assess whether or not anastrozole alone has any anticoagulant activity. METHODS: This was a randomized, double-blind, placebo-controlled, two-way crossover trial conducted at a single centre. The study comprised two treatment periods of 11 days, separated by a 3 week washout. Healthy male volunteers (n = 16, median age 28.5 years) were randomized to receive either anastrozole (7 mg loading dose on day 1, followed by 1 mg daily on days 2–11) in the first treatment period and placebo in the second treatment period, or vice versa. In addition to their randomized treatment, all volunteers received a single dose of 25 mg warfarin on day 3 of each treatment period. Blood samples for pharmacokinetic and pharmacodynamic assessment were taken at frequent intervals during each treatment period. The safety of volunteers was monitored throughout the study. RESULTS: Administration of anastrozole resulted in no clinically significant changes in the pharmacokinetics of either R- or S-warfarin compared with placebo for AUC (ng ml(−1) h) (glsmean, R-warfarin; anastrozole 93619.9, placebo 91127.91, 95%CI 0.988–1.068; S-warfarin; anastrozole 57129.21, placebo 55676.34, 95%CI 0.979–1.076), CL/F (ml min(−1)) (glsmean, R-warfarin; anastrozole 2.23, placebo 2.29, 95%CI 0.937–1.012; S-warfarin; anastrozole 3.65, placebo 3.74, 95%CI 0.929–1.021) and t(1/2) (h) (lsmean, R-warfarin; anastrozole 55.40, placebo 55.15, 95%CI−2.083–2.592; S-warfarin; anastrozole 39.38, placebo 40.98, 95%CI−6.189–2.996). In addition, anastrozole had no clinically significant effect on the pharmacodynamic effects of warfarin, as assessed 240 h after warfarin dosing by measurement of prothrombin time (s) (glsmean, anastrozole 11.56, placebo 11.31, 95%CI 0.987–1.059), thrombin time (s) (glsmean, anastrozole 19.06, placebo 18.75, 95%CI 0.980–1.054) activated partial thromboplastin time (s) (glsmean, anastrozole 29.94, placebo 29.74, 95%CI 0.968–1.047) and factor VII (%) (glsmean, anastrozole 97.81, placebo 107.26, 95%CI 0.821–1.012). Anastrozole alone had no effect on these indicators of the clotting process. CONCLUSIONS: Overall, there was no evidence to suggest that anastrozole has any clinically relevant effects on the pharmacokinetics of warfarin. Anastrozole had no effect on clotting mechanisms or on the pharmacodynamic activity of warfarin, as assessed by prothrombin time, thrombin time, activated partial thromboplastin time, and factor VII.